2014
DOI: 10.1088/0004-637x/784/1/53
|View full text |Cite|
|
Sign up to set email alerts
|

Observational Studies on the Near-Infrared Unidentified Emission Bands in Galactic H Ii Regions

Abstract: Using a large collection of near-infrared spectra (2.5-5.4 µm) of Galactic H II regions and H II region-like objects, we perform a systematic investigation of the astronomical polycyclic aromatic hydrocarbon (PAH) features. 36 objects were observed by the use of the infrared camera onboard the AKARI satellite as a part of a directer's time program. In addition to the well-known 3.3-3.6 µm features, most spectra show a relatively-weak emission feature at 5.22 µm with sufficient signal-to-noise ratios, which we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 57 publications
2
38
0
Order By: Relevance
“…The central wavelength of the absorption peak of CO 2 ice is slightly shorter than the typical value of 4.26 μm obtained in the same study, but it is still within the uncertainty due to the large noise level and the spectral resolution of the present observation. The absorption feature at around 4.67 μm is broader than the CO ice feature (Gibb et al 2004;Mori et al 2014). We fit it with both CO gas and ice components.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The central wavelength of the absorption peak of CO 2 ice is slightly shorter than the typical value of 4.26 μm obtained in the same study, but it is still within the uncertainty due to the large noise level and the spectral resolution of the present observation. The absorption feature at around 4.67 μm is broader than the CO ice feature (Gibb et al 2004;Mori et al 2014). We fit it with both CO gas and ice components.…”
Section: Resultsmentioning
confidence: 99%
“…We fit it with both CO gas and ice components. For CO ice, we adopt the central wavelength of 4.67 μm and the FWHM of 0.031 μm obtained from the Ns spectroscopy by Mori et al (2014) and assume the band strength reported in Gerakines et al (1995). The observed feature can be fitted by absorption of CO gas at 20 K and CO ice as shown in Figure 3(b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were taken from 399 lines of sight for 143 pointings, which were observed in the framework of Program DTIRC (PI: AKARI IRC team), IPYSO (PI: Takashi Shimonishi), and ISMGN (PI: Hidehiro Kaneda) during the AKARI Phase 3 period. Among them, the reduced data of http://pkas.kas.org Galactic H ii regions are released on the JAXA archive at: http://www.ir.isas.jaxa.jp/AKARI/Archive/ Catalogues/IRC_GALHII_spec/ (Mori et al, 2014). A study of part of the present dataset is also reported in Onaka et al (2016).…”
Section: Akari Nir Slit-spectroscopymentioning
confidence: 99%
“…Jones et al (2013) propose an interesting scenario for the evolution of carbonaceous dust grains, where they predict that carbonaceous dust tends to be aromatized in the ISM by the interstellar radiation and aliphatic C-H bonds are converted into aromatic C-H particularly for very small grains. Mori et al (2014a) study more than 160 lines of sight towards 36 Galactic H ii regions and H ii region-like objects with IRC NIR spectroscopy and derive the intensities of the emission bands originating from aromatic bonds at 3.3 µm and aliphatic bonds for 3.4-3.5 µm. The variation of the band ratio of aliphatic to aromatic bonds I(3.4 − 3.5 µm)/I(3.3 µm) is detected and found to be correlated with the ratio of the continuum intensity at 3.7 µm to the 3.3 µm band intensity I c (3.7 µm)/I(3.3 µm) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%